Products of Sulfide/Selenite Interaction Possess Antioxidant Properties, Scavenge Superoxide-Derived Radicals, React with DNA, and Modulate Blood Pressure and Tension of Isolated Thoracic Aorta. (25th November 2019) - Grman, Marian; Misak, Anton; Kurakova, Lucia; Brezova, Vlasta; Cacanyiova, Sona; Berenyiova, Andrea; Balis, Peter; Tomasova, Lenka; Kharma, Ammar; Domínguez-Álvarez, Enrique; Chovanec, Miroslav; Ondrias, Karol
Abstract : Selenium (Se), an essential trace element, and hydrogen sulfide (H2 S), an endogenously produced signalling molecule, affect many physiological and pathological processes. However, the biological effects of their mutual interaction have not yet been investigated. Herein, we have studied the biological and antioxidant effects of the products of the H2 S (Na2 S)/selenite (Na2 SeO3 ) interaction. As detected by the UV-VIS and EPR spectroscopy, the product(s) of the H2 S-Na2 SeO3 and H2 S-SeCl4 interaction scavenged superoxide-derived radicals and reduced ⋅ cPTIO radical depending on the molar ratio and the preincubation time of the applied interaction mixture. The results confirmed that the transient species are formed rapidly during the interaction and exhibit a noteworthy biological activity. In contrast to H2 S or selenite acting on their own, the H2 S/selenite mixture cleaved DNA in a bell-shaped manner. Interestingly, selenite protected DNA from the cleavage induced by the products of H2 S/H2 O2 interaction. The relaxation effect of H2 S on isolated thoracic aorta was eliminated when the H2 S/selenite mixture was applied. The mixture inhibited the H2 S biphasic effect on rat systolic and pulse blood pressure. The results point to the antioxidant properties of products of the H2 S/selenite interaction and their effect to react with DNA and influence cardiovascular homeostasis. The effects of the products may contribute to explain some of the biological effects of H2 S and/or selenite, and they may imply that a suitable H2 S/selenite supplement might have a beneficial effect in pathological conditions arisen, e.g., from oxidative stress.